Torto arado e corpo curvado: por um constitucionalismo costurado à terra como condição de efetividade do direito fundamental ao território quilombola - Oliveira, Júlio Tácio Andrade Lopes de (2023)
This dissertation analyzes the reasons that explain the (in)effectiveness, on the part of the Brazilian State, of guaranteeing the fundamental right to the territory, as a fulfillment of the commitment of historical reparation with the quilombolas assumed in the Federal Constitution of 1988, relating this situation to the official narratives in the History of Brazil. An institutional discourse prevails in Brazil that reproduces an image of the quilombo petrified in the past, distorted by racist stereotypes, and committed only to an exclusivist, individualistic, and negotiating model of territory. This perspective is confirmed when we analyze, critically, the expedients that the State uses so that this racist and asymmetric discourse can concretely increase the vulnerability of quilombola communities in Brazil. Thus, it seems important to situate coloniality as a constitutive face of Modernity, to unveil the ideologized institutional discursiveness and identify the contemporary modern technologies that represent today the continued historical murder of the quilombolas. The deconfiguration of the alienating discourse will make it possible to emerge, from the account of the oppressed, the historical experience and trajectory of the quilombos, which, by articulating the struggles for rights to territoriality, broadens the concept of rights such as property, freedom, and equality, contributing to the sizing of an effectively Brazilian constitutionalism. To this end, the dialectical and historical materialist method is used, due to its suitability for confronting concrete reality with idealistic conceptions that do not match reality. As a theoretical reference to face the problem, it adopts Walter Benjamin and Achille Mbembe, along with the Brazilian authors Beatriz Nascimento and Abdias Nascimento, with the contributions of the literary work "Torto Arado", by Itamar Vieira Júnior, an important methodological contribution to discuss the black quilombola agencies from the narratives about the formation of territorial bonds built around family relations, the relationship with the land and through memory. From these bases, it is observed, in Brazil, the existence of a Necropolitical State, which disrupts the implementation of the territorial public policy inserted in art. 68 of the ADCT and others, so necessary to these communities. It is necessary to understand who the quilombolas are in Brazil, both in their experiences of suffering and in the development of their ancestry. The quilombos open indispensable conditions for the construction of a project for an emancipating Brazil in the present, historically situated and committed to confronting the wounds of the past.